Language Features Used by Jeffree Star the Top English Speaker Beauty Vlogger - Xarista Eunice Alfanadha Mustika (Institute of Research and Community Outreach - Petra Christian University, 2022)
This study aims to find out the women’s and men’s language features used by Jeffree Star in his monologue entitled Full Face of Brands That Hate Me. The theoretical framework was based on Lakoff (2004) and Coates (2004) theories of language features. This study employed a qualitative approach. I found that Jeffree Star used color terms, adjectives, hedges, intonations, grammar, politeness, swear words, commands and directives, and questions. Jeffree Star also used two language features at the same time namely color terms and hedges, grammar and questions, swear words and hedges, and swear words and politeness. The use of language features by Jeffree Star was influenced by the topic of the talk and the gender identity. Further studies involving more subjects, objects, or other socio variables are needed to achieve a better understanding of the use of women’s and men’s language features. Keywords: language features, monologue, beauty vlogger